814 SLEEP DISORDERS AND DYSBIOSIS: CULPRITS IN CARDIOVASCULAR DISEASES. (15th December 2022) - Pala, Barbara; Pennazzi, Laura; Tifi, Priscilla; Volpe, Massimo; Tocci, Giuliano
Abstract: Introduction: Primary prevention of cardiovascular disease, the leading cause of death worldwide, has become a mainstay in addressing this considerable global challenge. It has become clear that the gut microbiome plays a vital role in human metabolism, immunity, and reactions to diseases, including cardiovascular disease. Growing evidence suggests that sleep quality can be influenced by the Gut Microbiome (GM), since probiotic supplementation has been found to improve subjective sleep healthy. Disruption of sleep and sleep/wake functions has been associated with both short (increased stress responsivity or psychosocial issues) and long term health consequences, including cancer and cardiovascular diseases. Emerging evidence suggests that disturbance of circadian rhythm, which incorporates essential physiological and humoral functions in a 24-hour cycle, could be an understudied risk factor for cardiovascular disease. While impaired sleep quality is a significant contributor to circadian rhythm disturbance, the evidence regarding sleep interventions and their effect on cardiovascular events is lacking. We conduct a literature review to synthesize a body of evidence on the interaction between sleep and GM in order to achieve robust and broad conclusions and implications with the cardiovascular system. Methods: We reviewed the literature on the relationship between sleep, gut microbiome and cardiovascular disease, from January 2017 up until August 2022. Results: The human GM can influence health through a bidirectional communication channel linking the brain and gut, the Brain-Gut-Microbiome Axis (BGMA). Many authors have described several underlying factors that could be involved in sleep-disorder, such as the immune system, the vagus nerve (VN), the neuroendocrine system, and bacterial metabolites. Furthermore, several interventions targeting the GM have been proved to be beneficial for amelioration of sleep problems: gamma-amino butyric acid (GABA) produced by the intestinal microbiota may influence the central nervous system through the VN and have an influence on sleep, as some studies reported Conclusions: Sleep health may constitute a novel cardiovascular risk factor and target for preventive intervention. More research and well-designed studies are needed to better evaluate the role of the microbiome in the multi-directional relationship between sleep, diet and CVD. From our analysis GM provides a wide range of potential therapeutic targets. Challenges ahead include the development of therapeutic interventions that target reversing gut dysbiosis, at an early stage, combined with good sleep behavior, which may open new horizons to prevent cardiovascular disease.